2015
DOI: 10.1074/jbc.m114.634667
|View full text |Cite
|
Sign up to set email alerts
|

Ectopically Expressed Pro-group X Secretory Phospholipase A2 Is Proteolytically Activated in Mouse Adrenal Cells by Furin-like Proprotein Convertases

Abstract: Background: GX sPLA 2 is expressed as an inactive pro-enzyme; the protease(s) responsible for pro-GX sPLA 2 processing are unknown. Results: Epitope-tagged pro-GX sPLA 2 is proteolytically activated by furin and PCSK6 in adrenal cells. Conclusion: Furin-like proprotein convertases regulate GX sPLA 2 activity. Significance: Identifying the factors involved in activating GX sPLA 2 provides novel insight into the mechanisms surrounding its regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Besides, furin AA genotype of rs4702 variant should be responsible for the regulation of BP through modulating furin levels in tissues other than peripheral blood [48]. In addition, Layne et al [49] demonstrated that furin modulates the production of corticosteroid in adrenal cells by cleaving group X secretory phospholipase A2 (GX sPLA2), implicating that furin may participate in the BP modulation. The mechanism underlying furinmediated regulation of BP may be associated with multiple aspects, such as the regulation of cytokine expression, sodium-electrolyte balance and renin-angiotensin system.…”
Section: Furin In the Regulation Of Blood Pressure (Bp)mentioning
confidence: 99%
“…Besides, furin AA genotype of rs4702 variant should be responsible for the regulation of BP through modulating furin levels in tissues other than peripheral blood [48]. In addition, Layne et al [49] demonstrated that furin modulates the production of corticosteroid in adrenal cells by cleaving group X secretory phospholipase A2 (GX sPLA2), implicating that furin may participate in the BP modulation. The mechanism underlying furinmediated regulation of BP may be associated with multiple aspects, such as the regulation of cytokine expression, sodium-electrolyte balance and renin-angiotensin system.…”
Section: Furin In the Regulation Of Blood Pressure (Bp)mentioning
confidence: 99%
“…As in the case of PLA2G1B (see later), PLA2G10 is synthesized as a zymogen, and removal of an N-terminal propeptide produces an active mature enzyme. This processing may occur extracellularly after secretion, as is the case for many digestive enzymes in the GI tract, or intracellularly before secretion by furin-like convertases (Jemel et al, 2011;Layne, Shridas, & Webb, 2015;Masuda et al, 2005). Among the sPLA 2 s, PLA2G10 has the highest affinity for PC and thus exhibits the most potent ability to hydrolyze plasma membrane phospholipids in intact cells (Bezzine et al, 2000;Murakami et al, 2001).…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…The sPLA 2 -X-dependent suppression of LXR can also occur in the adipose tissue, where Pla2g10 deficiency facilitates adipogenesis and obesity [ 48 ], and in the adrenal glands, where its deficiency promotes corticosteroidogenesis through the activation of steroidogenic acute regulatory protein [ 49 ]. In the latter case, pro-sPLA 2 -X is proteolytically processed to a mature, active form by the protein convertases furin and PCSK6, which are induced by the adrenocorticotropic hormone, in adrenal cells [ 50 ]. However, as far as we have been able to examine, the Pla2g10 expression in mouse macrophages and the adipose tissue is very low, arguing against the above observations.…”
Section: Introductionmentioning
confidence: 99%